The Increasing Students’ Vocabulary Through Spelling Bee Games - Dwi Nur Hadiyansah; M. Hilmy Hidayatullah; Mohammad Zainul Wahid (JOEY: Journal of English Ibrahimy, 2023)
This research aimed to find out whether a spelling bee game can increase students’ vocabulary or not and to find out the effectiveness of a spelling bee game to increase students’ vocabulary. The research method was classroom action research which consisted of cycles. The research location was in SMPN 1 Banyuputih. The data collection instruments were observation, documentation, questionnaire, and trial questions. Furthermore, the data were analyzed by qualitative descriptive and comparative descriptive. The conclusions of this research were spelling bee games can increase students’ vocabulary with the comparison test values 57,8 (Pre-test), 68,9 (Post-test 1), and 84,0 (Post-test 2). This game was also effective, it showed by the students’ activity observations results of 73% (1st meeting), 75% (2nd meeting), 77% (3rd meeting), and 92% (4th meeting) in a series. The questionnaire of effectivity also showed a value of 84,4 with the predicate good.